Developing a Wayang Sukuraga Pocket Book Media Based on a Deep Learning Approach to Enhance Students’ Critical Thinking Skills - Fauziah, Jembar Kitri; Nurasiah, Iis; Ramadhan, Rifky Aditya (Jurnal Paedagogy, 2026)
This study aims to develop learning media in the form of a pocket book integrated with the local wisdom of Wayang Sukuraga, based on Deep Learning, to improve critical thinking in Pancasila education among elementary school students. The study employed the Research & Development (R&D) model SAM, conducted in three iterations, with each iteration including evaluation, design, and development stages. The participants consisted of 26 fourth-grade students from an elementary school in Sukabumi City. Data were collected using expert validation questionnaires, student response surveys, and performance assessments on a 4-point Likert scale. Data were analyzed using paired-sample t-tests within a one-group pretest–posttest experimental design. Validation results showed high feasibility, with scores of 97.9% from subject matter experts, 97.5% from media experts, 97.2% from practitioner experts, and 90.41% from student responses. The overall average feasibility score was 95.75%, categorized as very valid. The paired-sample t-test revealed a significant improvement in critical thinking (Sig. (2-tailed) < 0.001), indicating that the Wayang Sukuraga pocket book is effective in enhancing critical thinking in Pancasila education. This media also serves as a prototype for integrating other forms of local wisdom into elementary school learning.